Entre tránsitos y rutas... la metodología del estudio (2011)
ABSTRACT: This article is intended to share some of the results of the investigation State of the art on theoretical and methodological foundation of professional intervention in social work and the conceptualization of experiences in the department of Antioquia, from 1998-2008, held at the under Line of Professional Social Work and Intervention Research Group Social Intervention Social Work Department of the Faculty of Social Sciences and Humanities of the University of Antioquia. In particular it seeks to recover in a thoughtful, methodological route built to identify the theoretical and methodological foundations of social work intervention from four Latin American countries (Argentina, Brazil, Chile and Colombia), in the period being 1998 to 2008. This reconstruction provides a novel process and relevant to the development of documentary research, there by contributing to the consolidation of the intervention as founding and structuring axis of the profession, claiming scientific status transformer scientific category, contributing in the positioning Social Work as a disciplinary field of Social Sciences.